Multi-Input Functional Encryption for Unbounded Arity Functions - Badrinarayanan, Saikrishna; Gupta, Divya; Jain, Abhishek; Sahai, Amit (ASIACRYPT, 2015)
The notion of multi-input functional encryption (MI-FE) was recently introduced by Goldwasser et al. [EUROCRYPT’14] as a means to non-interactively compute aggregate information on the joint private data of multiple users. A fundamental limitation of their work, however, is that the total number of users (which corresponds to the arity of the functions supported by the MI-FE scheme) must be a priori bounded and fixed at the system setup time. In this work, we overcome this limitation by introducing the notion of unbounded input MI-FE that supports the computation of functions with unbounded arity. We construct such an MI-FE scheme with indistinguishability security in the selective model based on the existence of public-coin differing-inputs obfuscation for turing machines and collision-resistant hash functions. Our result enables several new exciting applications, including a new paradigm of on-the-fly secure multiparty computation where new users can join the system dynamically.